THE EFFECTS OF TIME INTERVAL DIFFERENCES ON FEED EFFICIENCY, FEED CONVERSION RATIO AND FEED CONSUMPTION ON GOURAMI FISH SEEDS (Osphronemus gourami) - Ganjar Adhywirawan Sutardjo; Navis Jihanatul Faradilla; Haryadi Haryadi (Universitas Muhammadiyah Malang, 2023)
The main issues in gourami cultivation is the high need for feed. In order to reduce the high need for feed, a strategy that was applied is gastric emptying. This study aimed to find out the effective time for mastering gourami (Osphronemus gourami) and maximizing feed efficiency, minimizing feed conversion ratios, and minimizing the amount of feed consumption needed. This research was carried out by maintaining gourami in aquariums using 4 various times, one day get fed and one day off , two days get fed and one day off, three days get fed and one day off, and fed daily, each treatment was repeated 5 times. The method used in this study is an experimental method with a completely randomized design (CRD). Feed was given ad-satition method for 40 days. The main parameters used are feed efficiency, food conversion ratio (FCR), and number of feed consumption. Data on this study were analyzed by using variance analysis. The results showed that gastric emptying at different time intervals had no effect on feed efficiency, did not affect the food convergence ratio, and affected the amount of feed consumption followed by the smallest real difference test and it was found that P1 treatment had no significant effect, P2 treatment and P3 had significant effect, and P4 treatment really had a significant effect on treatment. Water temperature in this study ranged 26-28 ° C, and pH ranged from 7.9 to 8. Thus, the best amount of feed consumption is 73.60 grams in P3 (three days get fed and one day off), the best feed efficiency is in P3.